Imag(in)ing the war in Japan : representing and responding to trauma in postwar literature and film - Stahl, David C., 1959-; Williams, Mark, 1957- (Leiden ; Boston : Brill, 2010)
This study of a series of artistic representations of the Asia Pacific War experience in a variety of Japanese media is premised on Walter Davis' assertion that traumatic events and experiences must be 'constituted' before they can be assimilated, integrated and understood. Arguing that the contribution of the arts to the constitution, integration and comprehension of traumatic historical events has yet to be sufficiently acknowledged or articulated, the contributors to this volume examine how various Japanese authors and other artists have drawn upon their imaginative powers to create affect-
Introduction / David C. Stahl & Mark B. Williams -- Catastrophe, memory, and narrative : teaching Japanese and Jewish responses to twentieth-century atrocity / Alan Tansman -- Murakami Haruki and the war inside / Jay Rubin -- To make gods and demons weep : witnessing the sublime in 'Death in Midsummer' and 'Patriotism' / Dennis Washburn -- Writing the traumatized self : Tenkåo in the literature of Shiina Rinzåo / Mark Williams -- Okuizumi Hikaru and the mystery of war memory / Angela Yiu -- Victimization and 'response-ability' : remembering, representing, and working through trauma in Grave of the fireflies / David C. Stahl -- Fractious memories in Medoruma Shun's Tales of war / Davinder L. Bhowmik -- Framing the ruins : the documentary photographs of Yamahata Yåosuke (Nagasaki, August 10, 1945) / Mark Silver -- Responsibility and Japanese literature of the atomic bomb / Karen Thornber -- Of brutality and betrayal : youthful fiction and the legacy of the Asia Pacific War / Christine E. Wiley -- Contesting traumatic war narratives : Space Battleship Yamato and Mobile Suit Gundam / William Ashbaugh.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Japanese literature -- 20th century -- History and criticism; World War, 1939-1945 -- Japan -- Literature and the war; Motion pictures -- Japan -- History -- 20th century; World War, 1939-1945 -- Japan -- Motion pictures and the war; Psychic trauma in literature; Psychic trauma in motion pictures; Littérature japonaise -- 20e siècle -- Histoire et critique; Guerre mondiale, 1939-1945 -- Japon -- Littérature et guerre; Cinéma -- Japon -- Histoire -- 20e siècle.; Guerre mondiale, 1939-1945 -- Japon -- Cinéma et guerre; Traumatisme psychique dans la littérature.; Traumatisme psychique au cinéma.; LITERARY CRITICISM -- Asian -- General; Japanese literature; Motion pictures; Psychic trauma in literature; Psychic trauma in motion pictures; War and literature; War and motion pictures; Japan; Literatur; Zweiter Weltkrieg; Japan; Film; Literatur; Japanisch; Nachkriegszeit; Psychisches Trauma; 1900-1999; Criticism, interpretation, etc; History